Transpterygoid Approach to a Dermoid Cyst in Pterygopalatine Fossa - Ordones, Alexandre Beraldo; Fornazieri, Marco Aurélio; Pinna, Fábio de Rezende; Bezerra, Thiago Freire Pinto; Voegels, Richard Louis; Sennes, Luiz Ubirajara (International Archives of Otorhinolaryngology, 2014)
Objective To describe a case of dermoid cyst arising from the pterygopalatine fossa and review the literature.Methods We report a case of a 23-year-old man who suffered a car accident 2 years before otolaryngologic attendance. He had one episode of generalized tonic-clonic seizure and developed a reduction of visual acuity of the left side after the accident. Neurologic investigation was performed and magnetic resonance imaging revealed an incidental finding of a heterogeneous ovoid lesion in the pterygopalatine fossa, hyperintense on T2-weighted imaging.Results Endoscopic sinus surgery with transpterygoid approach was performed. The ovoid lesion was noted in the pterygopalatine fossa. Puncture for intraoperative evaluation showed a transparent thick fluid. Surprisingly, hair and sebaceous glands were found inside the cyst capsule. The cyst was excised completely. Histologic examination revealed a dermoid cyst. The patient currently has no evidence of recurrence at 1 year postoperatively.Conclusion This unique case is a rare report of a dermoid cyst incidentally diagnosed. An endoscopic transnasal transpterygoid approach may be performed to treat successfully this kind of lesion. Although rare, it should be considered in the differential diagnosis of expansive lesions in the pterygopalatine fossa, including schwannoma, angiofibroma, esthesioneuroblastoma, osteochondroma, cholesterol granuloma, hemangioma, lymphoma, and osteoma.
Keywords: dermoid cyst; epidermal cyst; head and neck neoplasms; skull base; nasal cavity; pterygopalatine fossa